Application of Reward and Punishment in Improving Employee Performance in The Development Administration Section of The West Aceh Regional Secretariat - Tuti Zulita; Said Achmad Kabiru Rafiie; Fadhil Fadhil (Universitas Medan Area, 2021)
This paper aims to find out how to apply rewards and punishments in improving employee performance in the Development Administration of Â West Aceh Regional Secretariat. The problem is focused on the provision of Rewards and Punishments, which have not gone well. To approach this problem, I used the theoretical references from Nnaji-Ihedinmah and Egbunik. The data were collected through a descriptive approach using interview, observation and documentation techniques and analyzed qualitatively. The results of this study are that the application of rewards in the Development Administration section has not been carried out properly. The provision of rewards was not given since there was no budget for giving rewards to employees. The employees only got performance benefits and allowances from existing programs. Rewards in the form of appreciation, neither financial nor non-financial awards were ever given to employees. Thus it can conclude that the employees want the application of these rewards to improve employee performance to be more motivated in doing work. The application of punishment, both in the development administration and during the morning meeting, has been carried out but has not gone well, there were still many employees who do not comply with the regulations that have been made, so it is necessary to carry out a more in-depth evaluation and improve the implementation of the rules more effectively and efficiently.